2008
DOI: 10.1136/emj.2007.053421
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous ketamine for adult procedural sedation in the emergency department: a prospective cohort study

Abstract: Ketamine is an effective agent for procedural sedation in the emergency department. There were no serious adverse events associated with its use, but there is a significant incidence of recovery agitation which may require treatment with a benzodiazepine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…It is true that emergence reactions appear to be more frequent in older pediatric patients and adults and that intraprocedural hypersalivation and postprocedural vomiting sometimes occur, risks of these complications can be mitigated by prophylactic measures (eg, benzodiazepines, antisialogogues, and ondansetron) [25]. In fact, the available adult sedation data regarding ketamineincluding cases in which the drug is administered in environments even more austere than the prehospital/HEMS setting-suggest both safety and efficacy of dissociative anesthesia in nonpediatric patients [26,27]. Emerging literature describing ketamine's use for trauma ETI in the ED is also suggesting the safety and even preferability of the agent, based on both physiology and simplicity (ie, single anesthetic plus NMB) [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is true that emergence reactions appear to be more frequent in older pediatric patients and adults and that intraprocedural hypersalivation and postprocedural vomiting sometimes occur, risks of these complications can be mitigated by prophylactic measures (eg, benzodiazepines, antisialogogues, and ondansetron) [25]. In fact, the available adult sedation data regarding ketamineincluding cases in which the drug is administered in environments even more austere than the prehospital/HEMS setting-suggest both safety and efficacy of dissociative anesthesia in nonpediatric patients [26,27]. Emerging literature describing ketamine's use for trauma ETI in the ED is also suggesting the safety and even preferability of the agent, based on both physiology and simplicity (ie, single anesthetic plus NMB) [17].…”
Section: Discussionmentioning
confidence: 99%
“…We chose ketamine, as discussed below, as a rescue agent for agitation and as an analgesic adjunct based on its use for sedation in emergency medicine and in the anesthesia literature as well as its differing mechanism of action than the medications she was currently receiving. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ketamine is an N-methyl-D aspartase (NMDA) receptor antagonist with known dissociative D. M. Noreika and P. Coyne 39 anesthetic properties. The analgesic and sedative effects that it produces are largely believed to be related to NMDA receptor blockade in the central nervous system and at the spinal cord level, although they additionally may be related to a complex interaction with opioid mu and kappa receptors.…”
Section: Discussionmentioning
confidence: 99%
“…which may last from 1 -3 hours. Strayer RJ et al, 2008 and Newton A et al 2008 [32,33] , reported side-effects of ketamine include tachycardia, hypertension, laryngospasm, emergence delirium, hypersalivation, increased in intraocular, intragastric and intracranial pressure. The risk of laryngospasm may be greater in dental patients as the procedure itself can stimulate the oropharynx, presence of secretion and blood in orophrynx can stimulate laryngeal reflexes.…”
Section: Benzodiazepines (Bzd)mentioning
confidence: 99%